Advancements in Research on Composite Bipolar Plates for Proton Exchange Membrane Fuel Cells - Wu, HanJie (Transactions on Engineering and Technology Research, 2024)
In proton exchange membrane fuel cells (PEMFC), the bipolar plate is a crucial component. Positioned between the anode and cathode, it supports the electrode reactions and provides pathways for gas flow. Made of conductive materials, it boasts excellent conductivity and mechanical stability, capable of withstanding the current generated by electrochemical reactions and resisting the corrosive and oxidative environments within the system. Thus, to ensure efficient energy conversion, the bipolar plate must exhibit good conductivity, mechanical strength, and corrosion resistance. This thesis systematically categorizes the selection of resins and graphite, based on a graphite-resin composite system, and compares the performance of various composite bipolar plates against the Department of Energy (DOE) standards. By examining the microstructure, the thesis explores the reasons behind these performance characteristics, aiming to determine the optimal graphite-resin ratio and modification methods.